2022
DOI: 10.1186/s40623-022-01621-6
|View full text |Cite
|
Sign up to set email alerts
|

Simple topographic parameter reveals the along-trench distribution of frictional properties on shallow plate boundary fault

Abstract: The critical taper model best describes the first-order mechanics of subduction zone wedges. The wedge geometry, which is conventionally defined by two parameters, slope angle and basal dip angle, accounts for the strength of megathrust. By applying this theoretical model, fault frictional properties and earthquake occurrences can be compared among subduction zones, and within a single subduction zone, and the spatial distribution or temporal change of fault strength can be investigated. Slope angle can be acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Wedge taper angles (surface slope α plus basal dip β) are largely controlled by the frictional strength of the décollement 40 . A recent theoretical study on critical taper model demonstrated that seafloor surface slope angle could be a first-order approximation to account for effective coefficient of basal friction for convergent margin wedge and thus the strength of décollement when the pore-fluid pressure ratio (λ) is high, internal friction (φ) is small, or both 41 . Koge et al 41 calculated WOA (weight of alpha (α)) of 70% based on (λ, φ) = (0.7, 27°), and therefore suggested that their method can be applicable to the Nankai outer accretionary wedge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wedge taper angles (surface slope α plus basal dip β) are largely controlled by the frictional strength of the décollement 40 . A recent theoretical study on critical taper model demonstrated that seafloor surface slope angle could be a first-order approximation to account for effective coefficient of basal friction for convergent margin wedge and thus the strength of décollement when the pore-fluid pressure ratio (λ) is high, internal friction (φ) is small, or both 41 . Koge et al 41 calculated WOA (weight of alpha (α)) of 70% based on (λ, φ) = (0.7, 27°), and therefore suggested that their method can be applicable to the Nankai outer accretionary wedge.…”
Section: Discussionmentioning
confidence: 99%
“…A recent theoretical study on critical taper model demonstrated that seafloor surface slope angle could be a first-order approximation to account for effective coefficient of basal friction for convergent margin wedge and thus the strength of décollement when the pore-fluid pressure ratio (λ) is high, internal friction (φ) is small, or both 41 . Koge et al 41 calculated WOA (weight of alpha (α)) of 70% based on (λ, φ) = (0.7, 27°), and therefore suggested that their method can be applicable to the Nankai outer accretionary wedge. We accepted their suggestion because the Nankai internal friction (φ = 27°) is much small although the pore-fluid pressure ratio (λ = 0.7) is not that high, compared to other 21 subduction zones with average values (λ, φ) = (0.88, 34°) for which the theoretical study was done.…”
Section: Discussionmentioning
confidence: 99%